A low complexity high efficiency hybrid multiplicative-additive crest factor reduction for OFDM systems - Al-Hussaini, Khalid; Mohd Ali, Borhanuddin; Varahram, Pooria; Hashim, Shaiful Jahari; Farrell, Ronan (Springer, 2017)
In this paper, we propose a novel technique to reduce the crest factor (CF) in orthogonal frequency division multiplexing systems. It consists of two inverse fast Fourier transform (IFFT) blocks, the input symbols of the first IFFT are the mapped symbols, whereas the input symbols of the second IFFT are the summations of the absolute value of the real part of the outer signal constellation points and zero symbols. First, the output of the two IFFT blocks is partitioned into four subblocks, which are subsequently used to rearrange the subblocks with padding zeros in a specific manner. Then, a new optimization scheme is introduced, in which only a single two-phase sequence and four iterations need to be applied. Numerical analysis shows that the proposed hybrid technique achieves better CF reduction performance with significantly lower complexity and better bit error rate performance than the existing scrambling (multiplicative) and additive CF techniques.